THE IMPACT OF SELF-ESTEEM ON JOB SATISFACTION: SOCIAL ANXIETY AS A MEDIATING VARIABLE-AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF TEACHERS IN THE FORMATIONS OF THE SOUTHERN TECHNICAL UNIVERSITY IN BASRA - Assistant Professor: Dr. Layla Laftah Ali; Amel Farhan Swadi (Scholars Digest Publishing, 2024)
The current research aims to identify important and vital behavioral variables in the business world, represented by self-esteem, job satisfaction, and social anxiety. The research was applied in the field at the Administrative Technical College in Basra, as it is one of the important formations at the Southern Technical University, and on a sample of teachers who hold master’s and doctorate degrees, numbering (313). ) Single. The questionnaire represented the main tool for collecting data, as it consisted of three axes that measured the variables of the study, the first related to self-esteem, the second related to job satisfaction, and the third related to social anxiety. The research was based on the main hypothesis that “there is a statistically significant effect of self-esteem on job satisfaction through the mediating variable social anxiety.” The data was analyzed using the AMOS statistical program and the SPSS program. The research reached a number of conclusions, the most important of which is that self-esteem is considered one of the important foundations for achieving job satisfaction in the organization, which in turn leads to achieving goals and achieving success. The study also proved that social anxiety has a significant impact on achieving job satisfaction. The research also came out with a number of recommendations, the most important of which is the necessity of Paying attention to the self-esteem of teaching staff, which contributes to achieving job satisfaction.
Keywords: self-esteem, job satisfaction, social anxiety